ANTIBIOTIC USAGE PROFILE IN MEDICINE WARD IN A TERTIARY CARE CENTRE OF WEST BENGAL - Sailayee Chaudhuri (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Antibiotics are one of the most commonly prescribed drugs in medicine wards for prophylactic and therapeutic purposes. irrational and indiscriminate use of antibiotics is a growing health hazard and this prescription of inappropriate drugs at inappropriate dose & duration needs to be checked.The objective of the study is to observe the pattern of antibiotic usage in the general medicine wards of Burdwan Medical College & Hospital and to assess the rationality of their use in terms of necessity, choice, dose, duration, route and number. it is a cross-sectional study including adult patients receiving antibiotic therapy either for therapeutic or prophylactic purpose during a study duration of 15days. Patients undergoing treatment for tuberculosis, malaria, filaria, HIV were excluded. Results showed among antibiotic prescribed in 381 patients, the maximum number was that of third generation Cephalosporin, the most common route of administration was parenteral. maximum number of antibiotics were prescribed therapeutically for respiratory tract infections and prophylactically for various gastrointestinal causes. Irrational antibiotic use was found in 35.8% of the cases of which CVA was the most common. Some serious lapses in antibiotic prescription pattern is seen in the study A strategic multidisciplinary approach needs to be established to optimize antimicrobial prescribing emphasizing on use of right drug at the right dose for the right duration & recognize when not needed which aims to improve the patient outcome